How Much Do Educators Teach – How Much Do Students Learn in Language and Literature Classes - Volkan Mutlu (Universal Journal of Educational Research, 2025)
Assessment is one of the crucial elements of language education because of its effects on the decisions taken at the end of the learning process. This makes it necessary to study it from various perspectives, one of which is the correctness of the results. By taking into this account, this study investigates the permanence of students’ acquisition, addressing a critical issue in educational assessment: the retention of material over time. Employing a time series version of the within-group experimental design, the study used 82 students selected through random and convenience sampling methods. These students took three different tests: a pre-test to measure initial knowledge, a formal final exam to grasp their knowledge after the instruction and understand whether they studied or not, and a subsequent test administered 20 days after the final exam. The findings reveal a substantial decline in retained knowledge, with students forgetting approximately half of the learned material. Additionally, while the type of questions used in the tests did not alter the overall results, it influenced the rate at which students forgot the material. This study underscores the need for more effective teaching or assessing strategies that promote long-term learning, especially when teaching theoretical knowledge.